Welfare Status of Indigenous Cattle in Terai and Mid-Hill of Nepal - Rana, K.P.; Kaphle, K.; Gautam, G. (Nepalese Veterinary Journal, 2018)
The aim of present study was to assess the status of welfare of indigenous cattle, based on certain animal-linked parameters: body condition (BCS), body hygiene (cleanliness), lameness, skin injuries, general condition, and flight distance. The study was ruled in eight herds (10 cows /herd) in Terai and Mid-hill region of Nepal from March to June 2014. Altogether 80 cattle kept in semi-intensive system were assessed using several indicators determined through specific methods. Out of 80 cattle, 2 (2.5%) had BCS between 1.5-2, considered as very thin cows; 49 (61.25%) had BCS between 2.25-2.75, considered as thin cows; 29 (36.25%) had BCS 3-3.75 considered as normal cows and no cows found with BCS more than 3.75 score; 69 (86.25%) had dung particles at their lower legs, 60 (75%) had dung particles at their flank region and 11(13.75%) had dung particles at their udder region; 4 (5%) were moderately lame, 27 (33.75%) had hairless spot on their different body parts(hock, knee joints, neck), 15 (18.75%) had swelling joints (knee joints); 10 (12.5%) showed fear at the observer’s approach. The general condition was good of all the assessed cows. The obtained results indicate that more than half of the assessed cows are thin and dirty which has a negative impact on their health and welfare. The main factors that affect the indigenous cattle welfare in Nepal are insufficiency of feeding, poor housing system, poor sanitation and hygiene maintenance, lack of treatment of injured/diseased cattle and somewhat poor human animal relationship.